(untitled) (Bangladesh Journal of Pharmacology, 2016)
Symplocos paniculata is a medicinal plant used by native healers to manage gastrointestinal ailments. The crude methanolic extract of S. paniculata was screened pharmacologically both in vitro and in vivo for the validation of its therapeutic potential. It suppressed the spontaneous activity of isolated rabbit jejunum preparations and also caused inhibition of the low K+ (20 mM)- induced spastic contractions in isolated rabbit jejunum preparations in a manner comparable to cromakalim. The relaxant effect was found to be blocked following glibenclamide exposure of the isolated tissue preparations similar to cromakalim, suggesting that observed response was likely to be mediated through opening of ATP dependent K+ channels. Following oral administration to mice provided protection against castor oil-induced diarrhea in a manner similar to loperamide. The plant material was found safe in toxicity study up to oral dose of 8 g/kg in mice. Hence, present study provides a scientific basis for the vernacular use of S. paniculata in gastro-intestinal system.